Prevalence of depression, anxiety and stress and associated workplace stressors among healthcare workers in a tertiary hospital in Vietnam: A cross-sectional study - Hoang-Phuong Nguyen; Thao Thi Phuong Nguyen; Ngoc Quang Nguyen; Thang Van Bui; Hai Anh Le; Van Thanh Hoang; Thanh Liem Nguyen (PLoS ONE, 2026)
Background Healthcare workers face disproportionate risks of depression, anxiety, and stress, yet evidence from private tertiary hospitals in Vietnam remains limited. We aimed to estimate the burden of psychological distress among healthcare workers and identify work-related correlates. Methods We conducted a cross-sectional survey of healthcare workers at tertiary hospital in Hanoi (n = 505; physicians = 151, nurses = 304, others = 50). The validated Vietnamese DASS-21 assessed depression, anxiety, and stress severity. Sociodemographic, occupational, and psychosocial factors were collected. Group differences were tested using chi-squared and Kruskal-Wallis tests. Ordinal logistic regression analyses using complete cases (n = 478) examined correlates of each DASS domain, adjusting for demographic, occupational, and workplace interaction variables. Results Overall, 30.3% of staff reported at least mild depressive symptoms, 28.7% at least mild anxiety symptoms, and 10.5% at least mild stress symptoms. Nurses exhibited the highest burden, with 34.9% reporting at least mild depression and 35.5% at least mild anxiety, compared with 21.2% and 16.0% among physicians and 30.0% and 26.0% among others, respectively. Stress symptoms were less prevalent (8.0% to 12.0%) and did not differ significantly across professional groups. In multivariable analyses, greater depression severity was associated with indefinite-term contracts and conflicts with patients or relatives; anxiety severity was associated with monthly income of 10–20 million VND and working in oncology; and stress severity was associated with caring for level II–III patients and contributing ≤50% of household income. Higher job satisfaction, supportive colleague relationships, perceived job stability, and greater continuing medical education exposure were associated with lower symptom severity across domains. Conclusions In this private tertiary hospital, nurses reported a higher burden of depressive and anxiety symptoms than physicians, whereas stress symptoms were less common and varied little across professions. Conflict prevention, support in high-acuity settings, continuing education, and a supportive team climate may be priorities for workplace mental health support.